Perbandingan Hasil Tangkapan Udang dengan Menggunakan Lapdu, Giltong Dan Trammel Net di Perairan Saengga Kabupaten Teluk Bintuni - Dahri Iskandar (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2010)
This experiment was carried out at Saengga Waters of Teluk Bintuni Regency using 6 (six) pieces of trammel net, lapdu and gilltong, respectively. The objective of this experiment was to compare catchability of trammel net, lapdu and gilltong for capturing shrimp. Total catch obtained in this experiment was 534 fishes which consist of 25 species. Dominant catch was banana prawn (Penaeus indicus) i.e 38.6% of total catch, followed by flatfish (Cynoglosus sp) and croaker fish (Cynoglosus sp) which consist of 17.04 % and 10.11 % of total catch, respectively. Dominant catch of gilltong and lapdu was dominated by fish while catch of trammel net was dominated by prawn. In term of Catch per Piece of Net, trammel net caught significantly large number of catch than gilltong and lapdu. Keywords: Trammel Net, Gilltong, Lapdu, Catch, Shrimp